Description of core excitations by time-dependent density functional theory with local density approximation, generalized gradient approximation, meta-generalized gradient approximation, and hybrid functionals - Imamura, Yutaka (Journal of computational chemistry, 2007)
Copyright 2007 Wiley Periodicals, Inc.